Gray's anatomy - Gray, Henry; Williams, Peter L.;Gray, Henry (Edinburgh ;;New York : Churchill Livingstone, 1989)
A comprehensive standard reference work with illustrations, descriptions, and definitions
Revised edition of: Anatomy, descriptive and surgical. 35th ed. 1973
Includes bibliographical references (pages 1477-1548) and index
Keywords: Anatomy; Human anatomy -- Anatomy